Supporting Children when Parents Separate : Embedding a Crisis Intervention Approach within Family Justice, Education and Mental Health Policy - Murch, Mervyn (Book collections on Project MUSE., 2018)
"After years of research and reflection on the work of the interdisciplinary family justice system Mervyn Murch offers a fresh approach to supporting the thousands of children every year who experience a complex form of bereavement following parental separation and divorce. This stressful family change, combined with the loss of support due to austerity cuts, can damage their education, well-being, mental health and long-term life chances. Murch argues for early preventative intervention which responds to children's worries when they first present them, without waiting until things have gone badly wrong. His radical proposals for reform involve a much more coordinated and joined up approach by schools, the Children and Family Court Advisory and Support Service, and Child and Adolescent Mental Health Services. This book encourages practitioners and academics to look outside their professional silos and to see the world through the eyes of children in crisis to enable services to offer direct support in a manner and at a time when it is most needed."--